Pengembangan Media Pembelajaran Interaktif Berbasis Discovery Learning Bermuatan Kearifan Lokal Pendap Bengkulu pada Materi Zat Aditif - Uliyandari, Mellyta; Sutarno, Sutarno; Nirwana, Nirwana (Jurnal Kajian Pendidikan IPA, 2025)
This study aims to develop interactive learning media based on discovery learning that integrates the local wisdom of Pendap Bengkulu in the topic of food additives, using the 4D development model, which consists of the stages of defining, designing, developing, and disseminating through YouTube and the Unib e-learning platform. The research instruments included validation questionnaires from material experts and media experts to assess product feasibility, student response questionnaires to measure practicality, as well as pretest and posttest to evaluate the effectiveness of the media. Validation results indicated that the media was categorized as highly feasible, with scores of 74 from the material expert, 56 from the media expert, and 35.76 from student assessments, supported by an average student response of 4.35 in the “agree” category. Effectiveness testing also showed an improvement in learning outcomes, as the average pretest score of 56.72 increased to 86.37 in the posttest, with a gain score of 0.68, which falls into the medium category. These findings confirm that the developed media is feasible and effective for use in science learning, while also contributing to the innovation of local wisdom-based media integrated with discovery learning to improve the quality of science education. Keywords: Interactive learning media, Discovery Learning, local wisdom, Pendap Bengkulu